Assessment of the Hardness of Various Orthodontic Wires - Yohan Verghese; Kumar Gaurav; Guneet Kour; Geetika Tomer; Subhrajeet Narayan Sahoo; Snigdha Pattanaik; Azhar Mohammed (Journal of Pharmacy and Bioallied Sciences)
Introduction: The mechanical characteristics of orthodontic wires are crucial since they have a significant impact on the effectiveness of orthodontic therapy, and patients undergoing orthodontic treatment are becoming more and more picky about their aesthetic preferences. Objectives: The goal of the current investigation was to assess the hardness of various orthodontic wires. Materials and Methods: Three types of wires were employed in this study: nickel titanium (NiTi, USA), beta-titanium (TMA, USA), and stainless steel (SS, Germany). For the upper left canine in this investigation, we utilized an edgewise bracket with a slot size of 0.018″. Epoxy resin was used to implant the wires. The orientation of the brackets was horizontal. Next, a measurement was taken of the brackets’ external surfaces’ hardness. Using an optical microscope, the micrographs of the typical Vickers indentations were captured. The acquired data was assessed statistically. Results: The specimens belonging to the stainless steel, nickel-titanium, and beta-titanium groups had mean microhardness values of 523.24, 367.22, and 321.36, respectively. There were noteworthy outcomes when comparing the three research groups. Conclusion: Among the stainless steel group specimens, the highest microhardness was observed. However, more research is advised.